Differential mRNA Expression and Circular RNA-Based Competitive Endogenous RNA Networks in the Three Stages of Heart Failure in Transverse Aortic Constriction Mice - Li, Xiang; Tan, Weijiang; Zheng, Shuang; Pyle, W. Glen; Zhu, Caiyi; Chen, Honghua; Kang, Le; Wu, Jian; Zou, Yunzeng; Backx, Peter H.; Yang, Feng Hua (Frontiers in Physiology, 2022)
Background The murine transverse aortic constriction (TAC) model is frequently used to investigate molecular mechanisms underlying heart failure. However, limited data is available regarding the expression of mRNAs and circRNAs in murine heart failure progression induced by pressure overload. Methods TAC was used to induce pressure overload for two, four, and eight weeks in mice. Echocardiographic measurements in B-mode and M-mode, as well as blood flow Doppler data were collected in mice without (sham) and with (2W-, 4W-, and 8W-post-TAC) pressure load. Hearts were excised and morphology, cardiomyocyte size, and fibrosis were determined. RNA sequencing, circRNA microarray, functional mRNA enrichment analysis, hub gene identification, target miRNA interaction, and competitive endogenous RNA (ceRNA) network construction were conducted. Results Heart weight, cardiomyocyte hypertrophy, and fibrosis gradually increased over time in the pressure overload hearts. The 2W-post-TAC hearts displayed concentric hypertrophy, thickened left ventricular walls, increased EF and FS. The 4W-post-TAC hearts was characterized by preserved EF and FS, dilated atria, increased left ventricle (LV) systolic volume. The 8W-post-TAC hearts presented with ventricular and atrial dilation, increased LV systolic and diastolic volume, reduced EF and FS, and increased ejection time (MV ET). mRNA expression analysis suggested cardiac remodeling, immune response dysregulation, and metabolic disorder were the key cellular events in heart failure progression. Depression in chemotaxis and mitochondrial function were predicted in 4W- and 8W-post-TAC myocardia, respectively. A ceRNA network analysis further demonstrated that the circRNAs targeted expression of matrix metallopeptidase, metabolic regulators, and adrenergic signaling in the 2W-post-TAC hypertrophic hearts, while they targeted expression of matrix regulators in the 4W-post-TAC EF-preserved hearts, and inflammatory regulation and a mitochondrial enzyme in the 8W-post-TAC EF-reduced hearts. Conclusions Our work empirically demonstrates that distinctive features of heart failure, including ventricular hypertrophy, heart failure with preserved EF (HFpEF), and heart failure with reduced EF (HFrEF) are present in the murine pressure overload models. The three stages of heart failure vary in terms of mRNA and circRNA expression, as well as ceRNA regulation in a manner consistent with their morphological, functional, and pathological differences.